Entrhogam blog, an efl teaching material based on gamification to sixth grade learners. (2020)
The present grade project is to receive the B.A. in Spanish and English. The project called ENTHROGAM (English Through Gamification) is purposed based on the learning necessities, and the results got by students of sixth grade at Sumapaz school in the Movers diagnostic test, which shows that they had lacked vocabulary. According to this argument, ENTHROGAM is established as an authoring tool designed as an educational blog on www.wix.com, to improve students´ vocabulary, which follows gamification principles. Gamification has been immersing in education context in schools, universities, and institutes, generating a new educational perception. This new perception has been a satisfactory impact; because, according to (Gabe & Christopher, 2011), “gamification is an integration of elements and mechanics game in activities that are not games”. Besides, gamification has educational benefits as generating a motivating learning environment, avoid frustration, and students can do a self- evaluation of their academic progress. It allows integrating ICT (Information Communication Technologies) as educational games and interactive platforms such as Kahoot, Quizizz, Educaplay, and Padlet. In the EFL (English as Foreign Language) teaching-learning process is also possible to involve fundamental aspects as Task-Based Learning Approach, critical thinking, and BLRs (Basic Learning Rights: English).